2006
DOI: 10.1039/b604726b
|View full text |Cite
|
Sign up to set email alerts
|

Threshold photoelectron photoion coincidence spectroscopy and selected ion flow tube cation-molecule reaction studies of cyclic-C4F8

Abstract: Using tunable vacuum-UV radiation from a synchrotron, the threshold photoelectron and threshold photoelectron photoion coincidence (TPEPICO) spectra of cyclic-C4F8 in the range 11-25 eV have been recorded. The parent ion is observed very weakly at threshold, 11.60 eV, and is most likely to have cyclic geometry. Ion yield curves and branching ratios have been determined for five fragments. Above threshold, the first ion observed is C3F5+, at slightly higher energy C2F4+, then successively CF+, CF2+ and CF3+ are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 43 publications
2
20
0
Order By: Relevance
“…The upper limit arises due to the possible presence of an exit-channel barrier and/or a kinetic shift; if both are zero, the conversion is exact. This procedure was developed for interpretation of photoionisation yields rather than state-selected TPEPICO yields, but we have shown that the procedure is equally valid for both experiments [29,30]. For the vibrational frequencies of SF 5 + and SF 4 Cl + needed for these conversions, values for the isoelectronic neutral molecules PF 5 and PF 4 Cl were used [31,32]; the differences of the vibrational frequencies due to a change in reduced mass of the sulphur and phosphorus analogues make negligible difference to these conversions.…”
Section: Data Analysis and Energeticsmentioning
confidence: 99%
“…The upper limit arises due to the possible presence of an exit-channel barrier and/or a kinetic shift; if both are zero, the conversion is exact. This procedure was developed for interpretation of photoionisation yields rather than state-selected TPEPICO yields, but we have shown that the procedure is equally valid for both experiments [29,30]. For the vibrational frequencies of SF 5 + and SF 4 Cl + needed for these conversions, values for the isoelectronic neutral molecules PF 5 and PF 4 Cl were used [31,32]; the differences of the vibrational frequencies due to a change in reduced mass of the sulphur and phosphorus analogues make negligible difference to these conversions.…”
Section: Data Analysis and Energeticsmentioning
confidence: 99%
“…The only ion which shows a significant variation from the TPEPICO branching ratios is N + (RE = 14.53 eV), as observed in previous work. 1,14 It appears that reaction with N + causes much 'softer' ionisation ( i.e. less fragmentation)…”
Section: Comparison Of Tpepico and Sift Branching Ratiosmentioning
confidence: 99%
“…1 The other investigated negative ion formation via electron attachment. 2 c-C 4 F 8 is used extensively in the dry etching of SiO 2 , but it has a high global warming potential.…”
Section: Introductionmentioning
confidence: 99%
“…Large isotope effects were observed for the reactions of CF 3 + , CF + and H 3 O + , cations with recombination energy (RE) less than the ionisation energy (IE) of C 2 H 2 Cl 2 , but small isotope effects were also observed for ions with RE values above the IE (C 2 H 2 Cl 2 ). We also compared the yields for each reaction to the ion yields from a photon-induced threshold photoelectron photoion coincidence (TPEPICO) study to determine the importance of long-range charge transfer in such reactions [3,4]. We have previously studied the reactions of these three isomers with small anions [5].…”
Section: Introductionmentioning
confidence: 99%